Pengaruh Profitabilitas dan Risiko Bisnis terhadap Dividend Payout Ratio melalui Likuiditas sebagai Variabel Moderasi - Salsabilla, Nadya Fernanda; Isbanah, Yuyun (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Dividend policy is a decision in which a company to determine the level of profit to be retained and the level of profits distributed as dividends to shareholders. This research aims to analyze the influence of profitability and business risk on dividend payout ratio with liquidity as moderating variable in Property, Real Estate, and Building Construction sector companies that is listed on the Indonesia Stock Exchange for the 2015-2018 period. The type of this research is a quantitative research and uses secondary data from the annual report on IDX. The sample of this research is 18 companies chosen by purposive sampling method. The data analysis technique used is multiple linear regression and moderated regression analysis (MRA). The results show that profitability has a positive effect on the dividend payout ratio because companies can utilize assets optimally to increase profits. Business risk harms the dividend payout ratio because companies choose to strengthen the capital structure and develop the companies by utilizing profits and investments to reduce business risk. After all, debt cannot always be expected. Liquidity can moderate the relationship between profitability and business risk on dividend payout ratios because liquidity is a consideration to dividend distribution so that it can increase the number of dividends distributed.